Refocusing Central Asia - Frantz Grenet (Collège de France, 2016)
The notion of Central Asia emerged at a late stage, replacing that of "Tartary", often associated with the Mongol Terror, in 1825 only. Two twentieth-century archaeological currents profoundly contributed to the revival of studies on this region: the French school led by the Délégation archéologique française en Afghanistan, and the Soviet school characterized by large multidisciplinary expeditions. The rediscovery of the region's two main languages, Sogdian and Bactrian, has significantly fu...